Reconstructing Bach: A Musical-Rhetorical Reinterpretation of His Violin Works - Chang, Yi-Li (Música Hodie, 2025)
During Renaissance and Baroque periods, composers and performers embedded musical rhetoric in performance practice. Interest in musical rhetoric then waned after Baroque period and was revived in the twentieth century. While music historians rediscovered and recognised its importance in the twentieth century, performers are only now beginning to understand how to apply musical rhetoric in their performances. Nevertheless, from a practical perspective, issues remain despite considerable scholarly discussion. Taking Johann Sebastian Bach’s (1680–1750) violin concerto in A minor (BWV 1041) as its example, this article discusses musical structure, framework and analytical interpretation through the lens of eighteenth-century musical rhetoric, thereby demonstrating that musical rhetoric was a common practice in eighteenth-century performances. By acquiring knowledge of musical rhetoric and analysing pieces with this concept in mind before playing, performers are suggested to interpret music in an appropriate and stylish manner that supports a more successful and expressive performance.